Utilization of Solar Energy in the Substation Energy in Provider Connected to PT. PLN (Persero) Based on IoT - Syanno Revy; Ahmad Taqwa; Fatahul Arifin (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
In organizing the Asian game event in Palembang in 2018, PT PLN Persero supported this activity by supplying electricity at several points in the Jakabaring Spot City (JSC) area with a total of 27 connecting substations with a loop system, but when the event was over the loop system was turned off and several locations of connecting substations. not deactivated due to operational constraints and the absence of activities at the location resulting in the supply to the substation shutting down but still operating distributing a voltage of 20 to several substations that are still operating in the JSC area, Indonesia has a very large renewable energy potential, especially solar energy which can supply a heater to maintain humidity prevent partial discharge and make cubicle equipment have a long lifetime. The results show that the radiation received by the PV system is sufficient to produce Stable electric power to turn on the heater continuously for 24 hours Future research will be extended to monitoring via IoT.